MENAKAR KEARIFAN LOKAL SUKU MALIND SEBAGAI MODEL PENANAMAN ECOLITERASI SISWA SEKOLAH DASAR DI KABUPATEN MERAUKE - Salman Alparis Sormin; Fredy .; Yonarlianto Tembang (Jurnal Education and Development, 2021)
This research departs from the current ecological issues, which are increasingly concerning. Not infrequently we see the issue of climate change become an interesting discussion in various circles. However, the facts of radical natural changes at this time are not accompanied by inclusive efforts to create an environmentally literate society. So through this study the author seeks to find ideas on how to transmit ecological awareness to students through social studies learning, especially in elementary schools. This research is anexploratory research with library research method, where research data is obtained from books, journals, notes and research reports that are relevant to this study. The analytical technique used in this study is data analysis using the Miles and Huberman model, which consists of data reduction, data presentation (display) and verification and conclusion (verification). Based on the results of the data analysis, it was found that the Malind tribe has local wisdom that can be used as a model for planting ecological intelligence in elementary school students. These local wisdoms include sasi adat and totemism. In addition to studying sasi rituals in class, sasi rituals can also be applied to maintain the cleanliness of the school environment, as well as totemism can be applied to train students' awareness of responsible attitudes to maintain and care for the environment.